Philosophic pride : Stoicism and political thought from Lipsius to Rousseau - Brooke, Christopher, 1973- (Princeton University Press, 2012)
Philosophic Pride is the first full-scale look at the essential place of Stoicism in the foundations of modern political thought. Spanning the period from Justus Lipsius's Politics in 1589 to Jean-Jacques Rousseau's Emile in 1762, and concentrating on arguments originating from England, France, and the Netherlands, the book considers how political writers of the period engaged with the ideas of the Roman and Greek Stoics that they found in works by Cicero, Seneca, Epictetus, and Marcus Aurelius. Christopher Brooke examines key texts in their historical context, paying special attention to the history of classical scholarship and the historiography of philosophy.